Factors associated with death and hospitalizations in patients with heart failure in a regional hospital in Peru - Arana-Morales, Guillermo (2026)
Introduction/Objective: To determine factors associated with death and hospitalizations in patients with heart failure (HF) at a regional hospital in Peru. Method: The following outcomes were evaluated: all-cause and cardiac death; hospitalizations. A total of 139 patients with HF seen in a cardiology clinic from April 2019 to April 2021 were evaluated. Their digital medical records were reviewed to obtain the required sociodemographic and clinical information. To assess the occurrence and time of the outcomes, their medical records were followed up until November 2022. Results: All-cause mortality: 15/100 person-years. Cardiac mortality: 7/100 person-years. Hospitalization rate: 9/100 person-years. In multivariate analysis, the hazard of all-cause death was higher in patients with higher functional class (FC), both crude and adjusted for sex and age. (crude HR 1.88 CI 1.14-3.01, p=0.014; adjusted HR 1.64 CI 0.99-2.71, p=0.054). The hazard of cardiac death was higher in patients with higher FC, both crude and adjusted (crude HR 4.04 CI 1.92-8.5, p=0.000; adjusted HR 3.66 CI 1.72-7.81, p=0.01). The hazard of hospitalizations was higher in patients with higher CF, both crude and adjusted (crude HR 4.29 CI 2.22-8.26, p=0.000; adjusted HR 4.32 CI 2.22-8.39, p=0.000). Conclusions: In patients with HF, all-cause mortality was 15/100 person-years, cardiac mortality 7/100 person-years, and hospitalization rate 9/100 person-years. CF is associated with all-cause mortality, cardiac mortality, and hospitalization.